2020
DOI: 10.1371/journal.pone.0244054
|View full text |Cite
|
Sign up to set email alerts
|

The adverse health effects of punitive immigrant policies in the United States: A systematic review

Abstract: Background Immigrants in the United States (US) today are facing a dynamic policy landscape. The Trump administration has threatened or curtailed access to basic services for 10.5 million undocumented immigrants currently in the US. We sought to examine the historical effects that punitive laws have had on health outcomes in US immigrant communities. Methods In this systematic review, we searched the following databases from inception–May 2020 for original research articles with no language restrictions: Ovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…In addition to identifying interpersonal and community levels of social support, future research must also continue to identify how community and macrolevels of discrimination contribute to mother–child health. For instance, structural discrimination, such as exclusionary immigrant policies, have been associated with heightened stress, parental distress, increased food insecurity (Perreira & Pedroza, 2019; Toomey et al, 2014; Vernice et al, 2020) and LBWs in infants of immigrant (Tome et al, 2021; Torche & Sirois, 2018) and US‐born Latina mothers (Novak et al, 2017). Future perinatal research in Latinas must account not only for measures of cultural adaptation but recognize how developmental exposures across the life span, including multiple ecological levels of discrimination, may be associated with adverse health trajectories for a mother and her child.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to identifying interpersonal and community levels of social support, future research must also continue to identify how community and macrolevels of discrimination contribute to mother–child health. For instance, structural discrimination, such as exclusionary immigrant policies, have been associated with heightened stress, parental distress, increased food insecurity (Perreira & Pedroza, 2019; Toomey et al, 2014; Vernice et al, 2020) and LBWs in infants of immigrant (Tome et al, 2021; Torche & Sirois, 2018) and US‐born Latina mothers (Novak et al, 2017). Future perinatal research in Latinas must account not only for measures of cultural adaptation but recognize how developmental exposures across the life span, including multiple ecological levels of discrimination, may be associated with adverse health trajectories for a mother and her child.…”
Section: Discussionmentioning
confidence: 99%
“…Although depressive symptom‐to‐symptom and symptom‐to‐biomarker relationships have been explored in pregnant Latinas using a nursing symptom science approach, symptoms were not contextualized in relation to psychosocial experiences (Santos et al, 2017). In fact, network analyses have not yet explored how Latinas may respond to and cope with psychosocial experiences although substantial evidence has entwined emotional and physical health with chronic societal stressors in Latinx populations (Vernice et al, 2020). These psychological pathways cannot be captured with depression sum‐scores.…”
Section: Introductionmentioning
confidence: 99%
“…Some factors that may contribute to this higher decline rate in accepting new therapies among underrepresented groups include a mistrust in the healthcare system, lack of resources (for example, concern for cost and travel means), concerns about residence and immigration status, medical misinformation and misconceptions, poor health literacy, lack of community engagement, and lack of appropriate language and cultural interpretation. [10][11][12][13][14][15][16][17] The inadequate representation of underrepresented populations in clinical trials may have also led to a lack of understanding of the effect of these factors on acceptance of treatment and resultant healthcare inequities. 18 Second, we observed that the social support system appears to be associated with the decision to accept or decline monoclonal antibody therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of scheduled vs. emergency-only dialysis in adult undocumented immigrants with ESKD has shown substantial cost savings when dialysis is provided in a planned and scheduled manner ( 15 ). Moreover, extending insurance coverage to undocumented immigrants and those who cannot afford to purchase insurance might lead to state and federal cost savings and improve the health of all U.S residents ( 72 74 ). Withholding kidney transplantation in children and young adults on dialysis due to an unfunded status is not only unethical but also increases morbidity and mortality.…”
Section: Summary and Policy Recommendationsmentioning
confidence: 99%